Biochemical Changes Induced by Gamma Irradiation in the Ground Beetle Blaps polycresta - Kheirallah, Dalia A.; El-Samad, Lamia M. (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
The exposure to low-dose gamma radiation from natural sources is a continuing and inescapable feature and it is common in certain occupations. The present study was designed to investigate the effects of low-dose gamma radiation on some detoxification enzymes such as; AST, ALT, ACP, ALP, GSH, GPX, SOD and CAT, as well as, its effect on total protein and DNA content in the soft tissues homogenate of males ground beetle Blaps polycresta. Insects were divided into three groups (group A, B and C) of 10 beetles each. Two groups (group B and C) were irradiated with doses at a rate of 32 Gy and 64 Gy; group A was considered as the control group. The study revealed a dose-dependent effect on the tested parameters. Significant increase in the enzyme activity of AST, ALT, ACP and ALP were observed in group B and C respectively compared to the control group (group A). The findings also showed a significant inhibitions in the enzymatic activity of GSH, GST, GPX, SOD and CAT in the irradiated groups compared to the control group. Furthermore, their radiated groups reported a decrease in protein and DNA content compared to the control group. Our observations suggested that the genotoxic effects of gamma radiation induced damaging effects on enzyme molecules, protein and nucleic acid (DNA) and may explain the increase in health risk from high doses of ionizing radiation.